2017
DOI: 10.1186/s12889-017-4387-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations between measures of socio-economic status, beliefs about back pain, and exposure to a mass media campaign to improve back beliefs

Abstract: BackgroundLow back pain (LBP) is one of the most common and costly healthcare problems worldwide. Disability from LBP is associated with maladaptive beliefs about the condition, and such beliefs can be influenced by public health interventions. While socioeconomic status (SES) has been identified as an important factor in health literacy and inequalities, not much is known about the association between SES and beliefs about LBP. Therefore, this study examined the relationship between measures of SES and the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 36 publications
(39 reference statements)
2
20
0
1
Order By: Relevance
“…This classification is partly insufficient: it is difficult to place education level, which is a socio-demographic background factor, into any of those categories. Socio-economic status is associated with back-related beliefs: those with high socio-economic status are more prone to believe that one should stay active regardless LBP [57]. Education level has been shown to affect adherence to exercise progression among people with chronic LBP [58], strength training [56], and leisure-time physical activity [59].…”
Section: Discussionmentioning
confidence: 99%
“…This classification is partly insufficient: it is difficult to place education level, which is a socio-demographic background factor, into any of those categories. Socio-economic status is associated with back-related beliefs: those with high socio-economic status are more prone to believe that one should stay active regardless LBP [57]. Education level has been shown to affect adherence to exercise progression among people with chronic LBP [58], strength training [56], and leisure-time physical activity [59].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that low economic class and financial concerns are associated with severe pain and widespread pain in several body regions [63][64][65][66][67][68]. In contrast, those with higher incomes tend to have a healthier life, live longer, and suffer less from illness and disability [69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients searching for information should be actively supported by their physicians. Future research should investigate the personal attitude and competences of physicians about knowledge transfer with an individual approach and also including community-based initiatives and mass media campaigns and HL [ 43 , 44 ]. Another aspect that should receive attention is the difference between the pain intensity measured by different instruments.…”
Section: Discussionmentioning
confidence: 99%